Constraints on subglacial melt fluxes from observations of active subglacial lake recharge - Malczyk, George; Gourmelen, Noel; Werder, Mauro; id_orcid:0 000-0003-0137-9377; Wearing, Martin; Goldberg, Dan (Cambridge University Press, 2023)
Active subglacial lakes provide a rare glimpse of the subglacial environment and hydrological processes at play. Several studies contributed to establishing active subglacial lake inventories and document lake drainage and connection, but few focused on the period between lake drainage when the melt production and transport contribute to the refilling of these lakes. In this study, we employ high-resolution CryoSat-2 altimetry data from 2010 to 2021 to compile an inventory of recharging lakes across Antarctica. We extract recharge rates from these lakes, which serve as a lower limit on subglacial melt production. These recharge rates are compared against predictions obtained by routing modelled subglacial meltwater at the ice-sheet's base. Our findings indicate that modelled recharge rates are consistent with observations in all but one of the investigated lakes, providing a lower bound on geothermal heat fluxes. Lake Cook E2 displays recharge rates far exceeding predictions, indicating that processes are taking place that are currently unaccounted for. Considering recharge in hydrologically connected lake networks instead of individually provides a stricter constraint on melt production. Recharge rates extracted from the Thwaites Lake system suggest that subglacial melt production has been underestimated. ISSN:0022-1430 ISSN:1727-5652